Electronic levels in silicon MaWCE nanowires: evidence of a limited diffusion of Ag. (1st October 2015) - Venturi, Giulia; Castaldini, Antonio; Schleusener, Alexander; Sivakov, Vladimir; Cavallini, Anna
Abstract: Deep level transient spectroscopy (DLTS) was performed on lowly n -doped silicon nanowires grown by metal-assisted wet chemical etching (MaWCE) with silver as the catalyst in order to investigate the energetic scheme inside the bandgap. To observe the possible diffusion of atoms into the bulk, DLTS investigation was also performed on the samples after removing the nanowires. Two of the four energy levels observed in the nanowires were also detected inside the substrate. Based on these results and on literature data about deep levels in bulk silicon, some hypotheses are advanced regarding the identification of the defects responsible for the energy levels revealed.